Evaluating and Enhancing a Campus Ministry Program Using Appreciative Inquiry - Rhean L. Sanchez (Randwick International of Education and Linguistics Science Journal, 2026)
This study evaluates the Campus Ministry Program of Mount Carmel College using Appreciative Inquiry as a framework for program evaluation and realignment. Anchored in qualitative action research, the study examined the program’s strengths, core life-giving factors, and areas for improvement based on the perspectives of 56 participants, including students, coordinators, and administrators. The Appreciative Inquiry 4-D Cycle (Discover, Dream, Design, and Destiny) was utilized to identify existing strengths and generate strategies for program enhancement. Findings revealed that the program is generally functional and contributes to students’ spiritual growth and personal development, particularly through operational activities such as retreats, practices, and exposure-based opportunities. However, leadership consistency, structured orientation, and member engagement were identified as areas needing improvement. The core life-giving factors valued by the youth include positive influence and community service, highlighting the program’s role in values formation and social responsibility. The study further identified actionable strategies such as strengthening leadership, improving orientation programs, enhancing youth-centered activities, and expanding community outreach initiatives. Sustainability of the program was found to depend on strong leadership commitment, active participation, continuous evaluation, and institutional support. The study concludes with the development of an enhanced Campus Ministry Program that is more responsive to contemporary youth needs, promoting holistic formation, community engagement, and values-driven leadership. The findings provide a basis for program improvement and offer insights for similar faith-based educational institutions.